Advances in antifouling strategies in membrane ultrafiltration: a brief review - Tahreen, Amina; Jami, Mohammed Saedi (Akademia Baru Publishing (M) Sdn Bhd, 2021)
This study briefly reviews the recent advances in membrane and separation technology for antifouling strategies for membrane ultrafiltration. Membrane fouling is inevitable in ultrafiltration due to the eventual membrane pore blockage with foulants. Consequently, flux declines and affects the membrane integrity over time along with elevation in processing time and thereby complicating the overall membrane maintenance. To combat this issue, several studies had been undertaken such as grafting of TiO2 nanotubes (TNTs), graphene oxide nanosheets, zwitterions or polymers in the membrane and also by applying direct current. Moreover, many researchers emphasized on the integration of an enhanced pre-treatment process such as adsorption, coagulation, electrocoagulation and so on. By critically analysing and comparing the existing studies, the impact, suitability, efficiency and sustainability of the antifouling strategies will be discussed in this review. This refined approach of observing the progress in membrane technology will enable the determination of the existing gaps in the studies and will help to expand and propel the field further in separation efficiency.